Ways Out of Liquidity Trap and Deflation - Frejtag-Mika, Eliza (Acta Universitatis Lodziensis. Folia Oeconomica, 2014)
This paper addresses the issue of liquidity trap. The term is adopted from J. Keynes to define an economy in the state of zero bound interest rate and imminent deflation. The discussion is based on findings from  P. Krugman’s theoretical model of an endowment economy (1998). Critical analysis is applied to recommendations for escaping from the liquidity trap which involves introduction of negative real interest rate by appropriate decisions of financial authorities aiming at structural reforms, fiscal and monetary expansion. This analysis, outlined in general terms by P. Krugman and his critics, focuses on critical assessment of theoretical consequences of discussed proposals, particularly those formulated as calls for “credible promises to be irresponsible”, and practical effects of escaping from the liquidity trap which has been undertaken by Japan, so far largely to no avail. Also, this paper presents the author’s evaluation of ways out of the liquidity trap attempted over the years and related to the current financial crisis, highlighting  the issues of inflation targeting, exchanges rates, and debt.